Integrative medical group visits for patients with chronic pain: results of a pilot single-site hybrid implementation-effectiveness feasibility study - Roth, Isabel; Tiedt, Malik; Miller, Vanessa; Barnhill, Jessica; Chilcoat, Aisha; Gardiner, Paula; Faurot, Keturah; Karvelas, Kris; Busby, Kenneth; Gaylord, Susan; Leeman, Jennifer (Frontiers in Pain Research, 2023)
Background Approximately 20% of adults in the United States experience chronic pain. Integrative Medical Group Visit (IMGV) offers an innovative approach to chronic pain management through training in mindfulness, nutrition, and other mind-body techniques combined with peer support. To date, there are no studies on IMGV implementation, despite its promise as a feasible non-pharmacological intervention for chronic pain management. In this study, we assessed the feasibility of implementing IMGV and assessing its effectiveness for chronic pain. Methods Implementation Mapping was used to develop and evaluate implementation strategies for IMGV. Strategies included disseminating educational materials, conducting ongoing training, and conducting educational meetings. IMGV was delivered by three healthcare providers: an allopathic physician, registered yoga teacher, and naturopathic physician. The effectiveness of IMGV on patient health outcomes was assessed through qualitative interviews and a Patient-Reported Outcomes Scale (PROMIS-29). Provider perspectives of acceptability, appropriateness, and feasibility were assessed through periodic reflections (group interviews reflecting on the process of implementation) and field notes. Paired t-tests were used to assess changes between scores at baseline and post intervention. Qualitative data were coded by three experienced qualitative researchers using thematic content analysis. Results Of the initial 16 patients enrolled in research, 12 completed at least two sessions of the IMGV. Other than fatigue, there was no statistically significant difference between the pre- and post-scores. Patients reported high satisfaction with IMGV, noting the development of new skills for self-care and the supportive community of peers. Themes from patient interviews and periodic reflections included the feasibility of virtual delivery, patient perspectives on acceptability, provider perspectives of feasibility and acceptability, ease of recruitment, complexity of referral and scheduling process, balancing medical check-in with group engagement, and nursing staff availability. Conclusions IMGV was feasible, acceptable, and effective from the perspectives of patients and providers. Although statistically significant differences were not observed for most PROMIS measures, qualitative results suggested that participants experienced increased social support and increased pain coping skills. Providers found implementation strategies effective, except for engaging nurses, due to staff being overwhelmed from the pandemic. Lessons learned from this pilot study can inform future research on implementation of IMGV.